The Knowledge, Service Features, Benefits, And Convenience and Their Influence on Customer Interest: Evidence on BSI Mojopahit 2 Mojokerto City, Indonesia: Pengaruh Pengetahuan, Fitur Layanan, Manfaat dan Kemudahan Terhadap Minat Nasabah dalam Menggunakan BSI Mobile Banking Pada Tahun 2021: Studi Pada BSI KCP Mojopahit 2 Kota Mojokerto - Alvina Mutia Hendarti; Ana Toni Roby Candra Yudha; Rianto Anugerah Wicaksono; Maksum Maksum; Nurul Huda (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
The development of technology is so rapid today that the banking industry must be able to provide services that can adapt to the needs and desires of customers in the current digital era, such as mobile banking. This study aims to determine the magnitude of the influence of knowledge, service features, benefits, and convenience on the interest of BSI Mojopahit 2 Mojokerto City customers in using BSI mobile banking in 2021. This study uses a quantitative research type with a sample of 100 respondents. The analysis used in this study is multiple linear regression analysis using the IBM SPSS 24 application. The results of this study show the multiple linear regression equation, namely Y = 1.433 + 0.175 X1 + 0.184 X2 + 0.219 X3 + 0.191 X4 + e. The F (simultaneous) test shows that the variables of knowledge, service features, benefits and convenience have a significant effect simultaneously or jointly on customer interest. Meanwhile, the T-test (partial) shows that the knowledge variable has a significant partial effect on customer interest. The service feature variable has a significant effect on the customer interest variable. The benefit variable has a significant effect on the customer interest variable, and the convenience variable significantly affects the customer interest variable. Moreover, the benefit variable is the variable that has the most dominant influence on the interest of BSI Mojopahit 2 Mojokerto customers in using mobile banking. Based on the results of this study, Islamic banking is expected to provide information about BSI mobile banking clearly and maintain and maximize service features, benefits and ease of use of mobile banking to increase customer interest so that the BSI mobile banking application becomes the main choice in transacting.